2016
DOI: 10.1002/ep.12336
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and accumulation characteristics of heavy metals in soil and plant from Huainan coalfield, China

Abstract: The distribution and accumulation behaviors of heavy metals in plants and corresponding soils in Huainan Coalfield, one of the national coal mine bases in China were investigated. Various plant species and corresponding soil samples were collected from three coal mines of different mining durations. The inductively coupled plasma mass spectrometry was employed to determine the concentrations of selected heavy metals (As, Cd, Cu, Ni, Pb, and Zn). The distribution characteristics of heavy metals in total plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Covering an area of about 450 km 2 , there are seven active coal mines in the research area: Zhou Zhuang, Qianyingyu, Qidong, Qinan, Luling, Zhuxianzhuang, and Taoyuan (Huang et al 2017). The study area has four distinct seasons, with windy, cold winters and rainy, hot summers.…”
Section: Study Areamentioning
confidence: 99%
“…Covering an area of about 450 km 2 , there are seven active coal mines in the research area: Zhou Zhuang, Qianyingyu, Qidong, Qinan, Luling, Zhuxianzhuang, and Taoyuan (Huang et al 2017). The study area has four distinct seasons, with windy, cold winters and rainy, hot summers.…”
Section: Study Areamentioning
confidence: 99%
“…This downward migration pattern has also been found in many studies [ 37 , 38 , 39 ]. Zhang et al [ 40 ] indicated that the metal accumulation in the surface soil would migrate to the bottom of the soil under long-term accumulation, weathering, and leaching, and showed a cumulative effect. The intensity and frequency of agricultural activities in M area were stronger than in H area of SD village.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have always paid attention to the distribution characteristics and pollution assessment of soil heavy metal in coal-mining cities [16,17]. On the basis of 30 coal-mining city samples from Deng et al [18], existing research about soil heavy metal has mainly focused on the partial land-use types of these cities, including the built-up area (e.g., Tongchuan, Fuxin, and Jinchang) [19][20][21], mining area (e.g., Xinzhuangzi mine and Panyi mine in Huainan, Suxian district in Chenzhou) [22,23], and farmland (e.g., Huaibei, Fuxin, and Shuangyashan) [24][25][26]. The sampling sites mostly adopted a triangular shape, hexagon shape, "S" shape, and "X" shape.…”
Section: Introductionmentioning
confidence: 99%